Four new species of Pomphopsilla Jałoszyński and a new record of Cephennodes glabella Castellini in the Democratic Republic of the Congo (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Four new species of the genus Pomphopsilla Jałoszyński are described, all based on specimens collected in the north-eastern part of DR Congo: P. pygmaea sp. n., P. pseudosoror sp. n., P. similis sp. n., and P. gumovskyi sp. n. Previously Pomphopsilla, represented by two species, was known to occur in Kenya; the only genera of Cephenniini recorded from DR Congo were Cephennodes Reitter and Cephennomicrus Reitter. Cephennodes (s. str.) glabella Castellini, so far known only from the type series, is recorded from the same region of Congo, based on numerous specimens collected by yellow pan traps. Because figures in the original description of this species were relatively schematic, the aedeagus and modifications of the head in the male are illustrated.